HUBUNGAN KEBIASAAN KONSUMSI MINUMAN ENERGY DRINK DENGAN KEJADIAN HIPERTENSI PADA BURUH ANGKUT DI PASAR PALMERIAM KOTA JAKARTA TIMUR TAHUN 2023 - Batubara, Saiful; Siregar, Julahir Hodmatua (Universitas Batam, 2023)
Background: Energy drink refers to drinks containing caffeine combined with other ingredients such as taurine, guarana and vitamin B, which are claimed to provide extra energy for users. The results of a study regarding the effects of energy drinks on healthy subjects aged 18-45 years, consuming 1-3 cans of energy drinks, the subjects experienced an average increase in systolic blood pressure of 3.5 mmHg and also had an average 10-msec prolongation in QT interval. Method: This research method is observational analytic with a cross sectional approach which was carried out at Palmeriam Market in East Jakarta City in 2023. The sampling technique in this research used a total sampling method with a sample size of 45 respondents. This research was carried out by collecting questionnaire data. Data analysis uses the Chi Square test. Result: The results of research on 45 respondents showed a significant relationship between consuming energy drinks and the incidence of hypertension in transport workers at Palmeriam Market in East Jakarta City in 2023. From the results of the Chi Square test, it was found that the p-value was 0.000 (p<0.05), so that H0 was rejected and Ha was accepted. Conclusion: Based on the results of this study, it can be concluded that there is a significant relationship between consuming energy drinks and the incidence of hypertension in transport workers at Palmeriam Market in East Jakarta City in 2023.